RELIGIOUS COMMITMENT OF CAREER PARENTS AND ITS CORRELATION WITH CHILDREN'S RELIGIOUS EDUCATION: A Case Study in Villa Nusa Indah 2 Palembang - Risfina, Almirah Meida; M. Sirozi; Amilda, Amilda (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
The purpose of this study was to determine the correlation between the level of religious commitment of career parents and the method of religious education given to their children in Villa Nusa Indah 2 Palembang Housing. This research uses descriptive correlational quantitative method. Purposive sampling was used in the sampling technique in this study, where there were 20 pairs of career parents and 20 children who were currently in elementary school education who lived in Villa Nusa Indah 2 Palembang. Data collection instruments used questionnaires, Likert scales of religious commitment and children's religious education methods. The data in this study were analysed using descriptive analysis techniques with statistical calculations in the form of frequencies and percentages and correlation analysis techniques using the Pearson Product-Moment correlation formula which was processed with the help of the SPSS version 25.0 for Windows computer program. Based on the results of data processing, there is a significant positive correlation between the religious commitment of career parents and the method of religious education given to children in Villa Nusa Indah 2 Palembang Housing with a correlation coefficient of 0.859. The positive coefficient number shows that the relationship between the two variables is unidirectional (unidirectional type of relationship), thus it can be interpreted that the higher the level of religious commitment of career parents, the more religious education is given to their children.